Transformative Pedagogy: Islamic Religious Education Model for Society 5.0 Amidst the Industrial Revolution - Parhan, Muhamad; Budiyanti, Nurti; Kartiko, Ari (Pascasarjana Universitas KH. Abdul Chalim, 2024)
The industrial society 5.0 revolution in Islamic Religious Education Learning can create the synergy that accelerates humans to adapt to changes that occur, by utilizing technological advances in learning. The Islamic Religious Education Model in learning is an effort made to answer increasingly complex and complex educational challenges in the era of the industrial revolution society 5.0 which requires the world of education to better prepare students to face the real world. This research uses a qualitative approach with a literature review method which aims to offer a model of Islamic Religious Education in the era of industrial society revolution 5.0. This learning model can help prepare students to face the real world, by directing students to the expectations they will achieve, the challenges they will face, and the abilities they need to master. So that the campus world can become a living laboratory for students in facing real life. Islamic religious education with this new model can be delivered flexibly (flexible learning) so that it will be more adaptive to changing times.